LØLAND, O. J. (2023), El apóstol de los ateos. Pablo en la filosofía contemporánea. Madrid: Trotta - Roldán, David (Daimon Revista Internacional de Filosofia, 2026)
Reseña de LØLAND, O. J. (2023), El apóstol de los ateos. Pablo en la filosofía contemporánea. Madrid: Trotta